(untitled) (AACINI - International Journal of Industrial Engineering, 2024)
The fragility of industrial agri-food chains has been more than evident. Phenomena such as natural disasters, wars, and pandemics, among other atypical events; have shown that the long food logistics chain cannot adapt to these phenomena to supply healthy and fresh food, promptly. Humanity is facing a constant change in the forms and modes of consumption. There is a transition towards the preference for the consumption of organic agricultural products, free of polluting chemical agents that are produced by the environment. In this sense, this document analyzes and discusses the system of Protected Agricultural production developed from Family Farming, as a scheme that allows from its characteristics the production and availability of fruits and vegetables throughout the year, for self-consumption or marketing. Protected Agriculture through the models: micro-tunnel, macro-tunnel, shade meshes, anti-insect meshes, anti-bird meshes, and greenhouses; are presented as a novel strategy that allows controlling part of the climatological factors, minimizing the impacts that environmental changes have on crops, as well as pests and diseases. Therefore, they are an alternative that allows for meeting the food supply in the face of atypical phenomena, and the current transformational context of society and modes of consumption.